Leigh Syndrome: A Comprehensive Review of the Disease and Present and Future Treatments - Giuseppe Magro; Vincenzo Laterza; Federico Tosto (Biomedicines)
Leigh syndrome (LS) is a severe neurodegenerative condition with an early onset, typically during early childhood or infancy. The disorder exhibits substantial clinical and genetic diversity. From a clinical standpoint, Leigh syndrome showcases a broad range of irregularities, ranging from severe neurological issues to minimal or no discernible abnormalities. The central nervous system is most affected, resulting in psychomotor retardation, seizures, nystagmus, ophthalmoparesis, optic atrophy, ataxia, dystonia, or respiratory failure. Some patients also experience involvement of the peripheral nervous system, such as polyneuropathy or myopathy, as well as non-neurological anomalies, such as diabetes, short stature, hypertrichosis, cardiomyopathy, anemia, renal failure, vomiting, or diarrhea (Leigh-like syndrome). Mutations associated with Leigh syndrome impact genes in both the mitochondrial and nuclear genomes. Presently, LS remains without a cure and shows limited response to various treatments, although certain case reports suggest potential improvement with supplements. Ongoing preclinical studies are actively exploring new treatment approaches. This review comprehensively outlines the genetic underpinnings of LS, its current treatment methods, and preclinical investigations, with a particular focus on treatment.